Azospirillum spp. biofertilization and corn, sorghum and wheat grain yield - Rangel Lucio, José Antonio; Ramírez Gama, Rosa María; Cervantes Ortíz, Francisco; Mendoza Elos, Mariano; García Moya, Edmundo; Rivera Reyes, J. Guadalupe (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
This manuscript argues about the Azospirillum spp. biofertilization profit, through grain yield of corn, sorghum and wheat tilled in Mexico. The assays were development in two different places. The seeds were inoculated with A. lipoferum or A. brasilense strains and later sowed. The results demonstrated a beneficial response to inoculation only for sorghum because of A. lipoferum VS-7 or VS-9 strains effect: the grain yield was significantly greater (55% and 49%) than nitrogen fertilizer effect. This result shown the affinity between sorghum plants and A. lipoferum VS-7 or VS-9 strains and the biofertilization potential use in a Mexico region where the agriculture production development a middle technology.